Powder metallurgy equivalent to 6063 forged aluminum alloy
A powdered metal composition replicating forged 6063 aluminum alloy properties addresses porosity issues, offering enhanced mechanical strength and thermal conductivity for applications like battery terminals and heat management.
Patent Information
- Application Number
- JP2024527802
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-14
- Filing Date
- 2023-01-12
- Publication Date
- 2025-02-04
AI Technical Summary
Existing powdered metallurgy processes struggle to replicate the mechanical and thermal properties of forged 6063 aluminum alloy, leading to issues such as porosity and reduced performance in manufactured parts.
A powdered metal composition comprising aluminum, silicon, magnesium, and optionally tin, with ceramic additives like aluminum nitride, is developed to mimic the properties of forged 6063 aluminum alloy, enhancing mechanical strength and thermal conductivity through controlled sintering and heat treatment.
The composition achieves mechanical characteristics comparable to forged 6063 alloy, with improved thermal conductivity and wear resistance, suitable for applications like battery terminals and heat management.
Smart Images

Figure 2025503374000001_ABST
Abstract
Description
[Technical Field]
[0001] (CROSS-REFERENCE TO RELATED APPLICATIONS) This application claims priority to U.S. Provisional Patent Application No. 63 / 299,649, filed January 14, 2022, entitled "Powder Metallurgy Equivalent to 6063 Wrought Aluminum Alloy," which is incorporated herein by reference.
[0002] This disclosure relates to powder metallurgy formulations and sintered parts produced therefrom. In particular, this disclosure relates to replacement powder metal compositions for wrought 6063 aluminum alloy. [Background technology]
[0003] 6063 aluminum alloy is a precipitation-hardened aluminum alloy containing magnesium (Mg) and silicon (Si) as the primary alloying elements. Within 6063 alloy, magnesium and silicon form the basis of the system's heat treatment, which enhances mechanical properties by forming the Mg2Si intermetallic phase. This results in excellent mechanical properties, thermal conductivity, weldability, and corrosion resistance. 6063 aluminum alloy can be soft anodized to achieve attractive color finishes and has excellent extrusion formability. 6063 aluminum alloy is used, among other applications, in automotive products, machine components, building construction, window and door frames, pipe and tubing, furniture, and various industrial process products. Its excellent thermal conductivity allows it to be used in applications where heat management is critical, such as battery terminals.
[0004] As used herein, 6063 aluminum alloy composition should be understood to mean, in weight percent, 0.2-0.6% silicon, 0.0-0.35% iron, 0.0-0.1% copper, 0.0-0.1% manganese, 0.45-0.9% magnesium, 0.0-0.1% zinc, 0.0-0.1% titanium, and up to 0.1% chromium, with the balance or balance being aluminum. As used herein, 6063A aluminum alloy composition should be understood to mean, in weight percent, 0.3-0.6% silicon, 0.15-0.35% iron, 0.1% copper, 0.15% manganese, 0.6-0.9% magnesium, 0.0-0.15% zinc, 0.1% titanium, and 0.05% chromium, with the balance or balance being aluminum. To understand the properties of 6063 aluminum alloy, selected mechanical and thermal properties of 6063 forged parts with processing conditions corresponding to various tempers (T5, T6, and T832) are provided as shown in Table 1 below. [Table 1] These properties are provided to provide a general understanding of the material properties of 6063 aluminum alloy in its tempered, forged form.
[0005] While the composition and material data for 6063 aluminum alloy above pertains to forged parts, the powder metal or "PM" process represents an alternative manufacturing technique for forming metal parts. Powder metallurgy generally involves producing or obtaining powdered metal material, compacting the powdered metal material in a set of tools and dies to form a green compact or preform having a shape approximating the desired final product, and then sintering the green compact to allow the powder metal particles to diffuse together and densify into a mechanically stronger object. Powder metallurgy is well suited to mass production of parts and offers the advantages of low scrap costs and the ability to produce parts that do not require post-forming machining.
[0006] While this is only a general overview of powder metal manufacturing processes, it can be understood from this description that many of the powder metal processes are typically carried out in the solid state or with a limited amount of liquid formed during the sintering process. However, this also highlights some of the challenges of using powder metal processes, such as the fact that sintering is a diffusion-dependent process, and therefore the resulting microstructure and porosity are a function of the powder formulation and processing conditions.
[0007] Therefore, attempts to convert wrought or cast alloys into powder metal formulations can pose challenges in both producing an equivalent microstructure and providing equivalent mechanical and / or thermal properties. Summary of the Invention
[0008] From the Background section above, it should be appreciated that many such wrought alloys cannot be produced by simply combining various elemental powders together, as their wrought counterparts, because powder metal processes rely on diffusion and the resulting morphology may not be similar to that of a wrought part having an otherwise similar chemical composition. Furthermore, because powder metal parts are various powders sintered together, some degree of porosity will typically be present after conventional sintering processes, and such porosity can adversely affect material properties compared to a fully dense part.
[0009] Therefore, there is a strong and currently unmet demand for powder metallurgical equivalents of wrought materials such as 6063 aluminum alloy compositions.
[0010] Disclosed herein is a powder metal composition equivalent to wrought 6063 aluminum alloy. This powder metal composition, comparable in performance to wrought 6063 aluminum alloy, adds another potential alloy to the toolbox of materials available for new applications using powder metallurgy and potentially opens the door to the production of parts from powder metal that have previously been limited to the production of wrought alloys. Such alloys may be particularly useful for the production of parts for electric vehicles, including battery terminals and other applications and products where thermal management is critical or necessary. Additionally, powder metal compositions and parts made therefrom may include the addition of metal matrix composite (MMC) additives to improve wear resistance and high-strength endurance.
[0011] According to one embodiment, a powder metal composition is provided that has been compacted, sintered, and heat treated to be equivalent to wrought 6063 aluminum alloy. The powder metal composition consists essentially of aluminum powder metal, aluminum-silicon powder metal, elemental magnesium powder metal, and optional elemental tin powder metal, free of pre-alloyed alloying additives, except for unavoidable ineffective trace materials. The powder metal composition may also have an optional ceramic powder additive (in addition to any lubricant present) to provide a metal matrix composite upon sintering, which is not considered when calculating the alloy percentage in the powder metal composition. If present, the ceramic additive can provide a metal matrix composite upon sintering, and the ceramic additive is not included in the calculation when calculating the alloy percentage of the powder metal composition. The powder metal composition further includes a lubricant, the weight of which is excluded from the weight percentage of each alloying element, because it is burned off during sintering of the powder metal composition. The weight percentage of silicon in the powder metal composition is in the range of 0.2% to 0.6% by weight of the powder metal composition, the weight percentage of magnesium in the powder metal composition is in the range of 0.5% to 0.9% by weight of the powder metal composition, and the weight percentage of tin (if present) in the powder metal composition is in the range of 0.0% to 1.0% by weight of the powder metal composition.
[0012] In some embodiments of the powder metal composition, the weight percentage of the silicon in the powder metal composition is within a narrower range of 0.3 wt % to 0.5 wt % of the powder metal composition, and the weight percentage of the magnesium in the powder metal composition is within a narrower range of 0.6 wt % to 0.8 wt % of the powder metal composition. Furthermore, in some specific embodiments, the weight percentage of the silicon in the powder metal composition is within a narrower range of 0.35 wt % to 0.45 wt % of the powder metal composition, and the weight percentage of the magnesium in the powder metal composition is within a narrower range of 0.65 wt % to 0.75 wt % of the powder metal composition. In yet another embodiment, the weight percentage of the silicon in the powder metal composition is 0.4 wt % of the powder metal composition, and the weight percentage of the magnesium in the powder metal composition is 0.7 wt % of the powder metal composition.
[0013] In some embodiments, the aluminum powder metal may be at least 99.7% by weight aluminum.
[0014] In some forms of the powder metal composition, the aluminum-silicon powder metal may be an Al-12Si master alloy powder metal having 88% aluminum and 12% silicon by weight.
[0015] In some embodiments, the weight percentage of tin in the powder metal composition (when tin powder metal is present) is within the narrower range of 0.25% to 0.75% by weight of the powder metal composition. More specifically, in some specific embodiments, the weight percentage of tin in the powder metal composition may be within the range of 0.25% to 0.5% by weight of the powder metal composition, or may be specified as 0.25% or 0.5% by weight of tin.
[0016] In some embodiments, the lubricant may be present in an amount of 1.5 wt.% of the total weight of the powder metal composition, although, as noted above, because the lubricant is substantially or completely burned off during sintering, the weight of the lubricant is not included in the weight of the powder metal composition when calculating the percentage of the alloy.
[0017] In some embodiments, the ceramic additive, if present, may comprise less than 15% by volume of the powder metal. Again, the weight of the ceramic powder additive is not included when calculating weight percentages, since when ceramic is added, it forms the matrix of the metal matrix composite from which the metal is made. The ceramic powder additive may be aluminum nitride. The aluminum nitride may be 2.0 m 2 The aluminum nitride (AlN) may have a specific surface area of 1.8 μm or less, a particle size distribution at D 10% in the range of 0.4 μm to 1.4 μm, a particle size distribution at D 50% in the range of 6 μm to 10 μm, and a particle size distribution at D 90% in the range of 17 μm to 35 μm. 2 / g to 3.8m 2 / g, with a D10% particle size distribution in the range of 0.2 μm to 0.6 μm, a D50% particle size distribution in the range of 1 μm to 3 μm, and a D90% particle size distribution in the range of 5 μm to 10 μm. The aluminum nitride (AlN) may have a hexagonal crystal structure and be single phase. However, other forms of ceramic powder additives, such as, but not limited to, Al2O3 or SiC, may be used instead.
[0018] According to another aspect, a green compact is formed from the powder metal composition described above and herein. While the specific compaction pressure may vary, it is contemplated that the compaction pressure may be in the range of 250 MPa to 550 MPa, with the target compaction pressure potentially being in the range of 250 MPa to 350 MPa.
[0019] According to a further aspect, a sintered powder metal part may be formed from the compact described in any of the above aspects and herein. The sintered powder metal part may have a thermal conductivity in the range of 190 W / (m·K) to 205 W / (m·K) within a temperature range of 100°C to 200°C. This provides excellent thermal conductivity for a sintered powder metal part, making the composition highly suitable for applications where thermal performance is a consideration. Furthermore, the powder metal part may have an ultimate tensile strength in the range of 100 MPa to 140 MPa and / or a yield strength in the range of 90 MPa to 105 MPa. These mechanical properties indicate that the powder metal composition can be used to produce parts with mechanical properties comparable to those of 6063 forged parts.
[0020] These and other advantages of the present invention will become apparent from the detailed description and drawings. The following is merely a description of some preferred embodiments of the present invention. These preferred embodiments are not intended to be the only embodiments covered by the claims, and reference should be made to the claims to assess the full scope of the invention. [Brief explanation of the drawings]
[0021] [Figure 1A] FIG. 1 shows the percent theoretical density of various samples of powder metal parts compacted at 250 MPa and sintered for 20 minutes at various sintering temperatures from 610° C. to 640° C. in 5° C. increments. All sintered powder metal part samples contained 0.4 wt. % silicon, 0.7 wt. % magnesium, 0.0 wt. %, 0.25 wt. %, 0.5 wt. %, and 1.0 wt. % tin (as indicated in the figure), with the remainder being aluminum made from a blend of aluminum powder metal, aluminum-silicon master alloy powder metal, elemental magnesium powder metal, elemental tin powder metal, and lubricant. [Figure 1B] 1B is a chart showing the average hardness of each of the as-sintered samples shown in FIG. 1A as a function of sintering temperature and tin content. [Figure 1C] FIG. 1B shows the percent mass change of the various sintered samples shown in FIG. 1A as a function of sintering temperature and various tin contents as indicated. [Figure 1D] FIG. 1B shows the percent dimensional change of the various sintered samples shown in FIG. 1A as a function of sintering temperature and various tin contents as indicated. [Figure 2A] 1 is a chart showing the effect of compaction pressure (150 MPa, 250 MPa, 350 MPa, 450 MPa, and 550 MPa) and tin content on the green strength of compacts having an Al-0.4Si-0.7Mg-xSn composition, where "x" in xSn is a tin content of 0.0, 0.25, 0.5, or 1.0 wt%. The horizontal line at 7500 kPa indicates the target green strength. [Figure 2B] FIG. 1 shows the effect of compaction pressure on sintered density for samples sintered at 635° C. for 20 minutes, for various compaction pressures and tin contents. [Figure 2C] 1 is a chart showing the effect of compaction pressure on average hardness for Al-0.4Si-0.7Mg-xSn compositions having various tin contents (where "x" in xSn is one of 0.0 wt%, 0.25 wt%, 0.5 wt%, and 1.0 wt%). [Figure 2D] FIG. 1 shows the effect of compaction pressure and tin content on the mass change rate during a sintering period of 20 minutes at 635°C. [Figure 2E] FIG. 1 shows the effect of sintering temperature and tin content on the mass change rate within a sintering period of 20 minutes at 635° C. [Figure 3A] FIG. 1 shows the effect of sintering time and tin content on density for aluminum alloy parts having a composition of Al-0.4Si-0.7Mg-xSn, where "x" in xSn is a tin content of any one of 0.0 wt. %, 0.25 wt. %, 0.5 wt. %, and 1.0 wt. %, which were compacted at 350 MPa and sintered at 635°C for the indicated durations. [Figure 3B]3B is a chart showing the effect of sintering time and tin content on the average hardness of the sintered part shown in FIG. 3A. [Figure 3C] FIG. 3B shows the effect of sintering time and tin content on the mass change of the sintered part shown in FIG. 3A. [Figure 3D] FIG. 3B illustrates the effect of sintering time and tin content on the dimensional change of the sintered part shown in FIG. 3A. [Figure 4A] FIG. 1 shows the effect of sizing pressure on sizing shrinkage for aluminum alloy parts having a composition of Al-0.4Si-0.7Mg-xSn, where "x" in xSn is a tin content of 0.25 wt % or 0.5 wt %, which are compacted at 350 MPa and sintered at 635°C for 20 minutes. [Figure 4B] FIG. 4B is a diagram showing the effect of sizing pressure on the theoretical density of the portion in FIG. 4A. [Figure 4C] FIG. 4B is a diagram showing the effect of sizing pressure on the average hardness of the portion in FIG. 4A. [Figure 5A] 1 is a chart showing the effect of elemental tin on Young's modulus for an aluminum alloy part having a composition of Al-0.4Si-0.7Mg-xSn, where "x" in xSn is any one of 0.0 wt. %, 0.25 wt. %, 0.5 wt. %, and 1.0 wt. % tin, formed at 350 MPa, sintered at 635°C for 20 minutes, and sized at 120 MPa in an unconstrained die, and comparing these values with those of a forged sample with an unspecified temper. [Figure 5B] 5B is a chart showing the effect of elemental tin on the ultimate tensile strength of the powder metal portion of FIG. 5A and comparing these values with those of 6063 aluminum alloy forgings T1 and T5 as reported in the literature. [Figure 5C] 5B is a chart showing the effect of elemental tin on the yield strength of the powder metal part of FIG. 5A and comparing these values with those of 6063 aluminum alloy forgings T1 and T5 as reported in the literature. [Figure 5D]5B is a chart showing the effect of elemental tin on the maximum elongation of the powder metal part in FIG. 5A and comparing these values with literature values for 6063 aluminum alloy forgings T1 and T5. [Figure 6A] 1 is a chart showing the effect of different heat treatment conditions on Young's modulus for a sample having a composition of Al-0.4Si-0.7Mg-xSn, which is sintered and sized, and which is subjected to heat treatment T8, which involves compacting at 350 MPa, sintering at 635°C for 20 minutes, solutionizing at 520°C for 2 hours, sizing in an unconstrained die at 120 MPa, and aging at 175°C for 22 hours. These values are compared to values for forgings of 6063 aluminum alloy parts subjected to heat treatment T8 and to non-specific heat treatments described in the literature. [Figure 6B] FIG. 6B is a chart comparing the effect of different heat treatment conditions on the ultimate tensile strength of the sample in FIG. 6A and comparing these to values for forgings of 6063 aluminum alloy parts that have been subjected to heat treatment T8, heat treatment T1, or heat treatment T5. [Figure 6C] FIG. 6C is a chart showing the effect of different heat treatment conditions on yield strength for the sintered powder metal samples shown in FIGS. 6A and 6B and comparing these with the values for the various forged samples shown in FIG. 6B. [Figure 6D] 6B is a chart showing the effect of different heat treatment conditions on maximum elongation for the sintered powder metal sample shown in FIG. 6A and comparing this with the values for forged samples with various heat treatment conditions. [Figure 7A] The natural ageing curves for the Al-0.4Si-0.7Mg-xSn composition, where "x" in xSn is tin content of 0.25 wt% or 0.5 wt%, are shown when the parts are compacted at 350 MPa and sintered at 635°C for 20 minutes. [Figure 7B]For the sample with a tin content of 0.5 wt. % in FIG. 7A, the curve for aging process T8 is shown, in which the sample is solution-heated at 520°C for 2 hours, subjected to a sizing reduction of 3.5%, and artificially aged at 175°C. [Figure 8A] Figure 1 shows the thermal conductivity over a range of temperatures for Al-0.4Si-0.7Mg-xSn compositions, where "x" in xSn is any one of 0.0, 0.25, 0.5, and 1.0 wt% tin, and compares these thermal conductivity values with those of a forged 6063 sample subjected to the T5 heat treatment. [Figure 8B] The thermal conductivity over a range of temperatures is shown for the composition Al-0.4Si-0.7Mg-0.5Sn, the effect of heat treatment T8 on this composition and a comparison with parts that were only sintered and sized, and these values are compared to 6063 forged samples subjected to heat treatment T5 or heat treatment T8. [Figure 9A] Figures are provided showing the as-sized surfaces of samples of Al-0.4Si-0.7Mg-0.5Sn ("PM 6063", left column) and Al-0.4Si-0.7Mg-0.5Sn with 1 vol.% AlN ("PM 6063-AlN", right column). [Figure 9B] Figures are provided showing the as-polished surfaces of samples of Al-0.4Si-0.7Mg-0.5Sn ("PM 6063", left column) and Al-0.4Si-0.7Mg-0.5Sn with 1 vol.% AlN ("PM 6063-AlN", right column). [Figure 9C]The images show the before and after anodizing process for samples of Al-0.4Si-0.7Mg-0.5Sn ("PM 6063") and Al-0.4Si-0.7Mg-0.5Sn with 1% AlN by volume ("PM 6063+1% AlN"); the untreated samples show the as-sized surface. The hard-anodized surfaces appear black (two samples per material composition and surface type), while the clear-anodized surfaces maintain a gray appearance (one sample per material composition and surface type). [Figure 9D] Before and after anodization are shown for samples of Al-0.4Si-0.7Mg-0.5Sn ("PM 6063") and Al-0.4Si-0.7Mg-0.5Sn with 1% AlN by volume ("PM 6063+1% AlN"); the untreated samples were polished with 240-grit SiC paper. The hard-anodized surfaces appear black (two samples per material composition and surface type), while the clear-anodized surfaces maintain their gray appearance (one sample per material composition and surface type). [Figure 10A] FIG. 1 shows the thickness and profile of the anodized layer of a hard anodized sample of PM 6063 after sizing. [Figure 10B] FIG. 1 shows the thickness and profile of the anodized layer of a hard anodized sample of "PM 6063+1% AlN" after sizing. [Figure 10C] FIG. 1 shows the thickness and profile of the hard anodized layer of a polished sample of "PM 6063." [Figure 10D] FIG. 1 shows the thickness and profile of the hard anodized layer of a polished sample of "PM 6063+1% AlN." DETAILED DESCRIPTION OF THE INVENTION
[0022] The powder metal compositions described herein are intended to provide mechanical and / or thermal properties comparable to those of forged parts made from 6063 aluminum alloy material. As described below, exemplary powder metal compositions and several variations thereof are disclosed. Additionally, various processing conditions and their effects on the mechanical and thermal properties of the resulting parts are explored. While alloying element additions clearly differ from the powder metal compositions and standard 6063 forgings, comparisons of certain mechanical and thermal properties suggest that such powder metal formulations may provide a replacement for 6063 forgings in certain applications.
[0023] The powder metals were blended to arrive at a base alloy composition of aluminum (bulk), 0.7 wt. % magnesium, and 0.4 wt. % silicon of the powder metal alloy composition. Tin was the only variable in the formulations investigated, and samples were prepared with no tin, 0.25 wt. % tin, 0.5 wt. % tin, and 1.0 wt. % tin. In addition to the blended powder metals, a lubricant was added, and, although data not provided here, it is conceivable that a ceramic powder could also be added to form a metal matrix composite.
[0024] It should be noted that the alloy percentages mentioned above are weight percentages of the total aluminum alloy powder metal composition, which includes only the metal additives. For powder metal compositions that contain other components, such as lubricants (waxes and / or binders, e.g., LicoWax® C) or ceramic additives, these non-metallic components are not considered as part of the alloy percentage. This is because, to the extent that the lubricant is present, it will be burned off during the sintering process. With regard to ceramic powder additives, these ceramic additives are excluded from the weight percentage calculation because they create a metal matrix composite (MMC), and the alloy percentage of the metal, not the total weight percentage of the elements in the MMC part, characterizes the metal matrix.
[0025] To arrive at the above-mentioned Al-0.7Mg-0.4Si-xSn composition, the components shown in Table I below are mixed in the prescribed proportions to produce the desired powder metal composition. [Table 2] Here, ECKA Granules GmbH is located in Velden, Germany, Tangshen Weihao Magnesium Powder Co. is located in Qian'an City, Hebei Province, China, and Clariant Corporation is located in Louisville, Kentucky, USA. While the exact powder quantities are not provided here, given the powder metal "ingredient" list for each formulation or variation, it is easy to work backward to find the exact ratios of powder metals to be combined in each case.
[0026] Lubricant additives make up only a relatively small percentage of the total weight of the powder metal composition. Traditionally, lubricants are added in an amount of 1.5 wt.% of the total weight of the mixed powders. The lubricant is a wax, such as LicoWax® C, which can help hold the formed green part together by holding the powder particles together and can also help remove the green part after compaction as it is ejected from the tool or die set. The lubricant is usually burned off during the sintering process in a preheat zone.
[0027] It should be noted that while magnesium and (optionally) tin are added as elemental powder metal additives, silicon is added as part of an 88 wt. % aluminum and 12 wt. % silicon master alloy powder. This represents a composition that reflects an aluminum-silicon eutectoid composition. Tin can help catalyze the densification response of powder metal alloys and was investigated for this reason. Therefore, for the avoidance of doubt in Table I, the Al-Si powder described above is an Al-12Si master alloy powder.
[0028] It is contemplated that the powder metal composition (or at least the metal component of the metal powder) may include only these listed powder metals (aluminum, Al-12Si, magnesium, and optionally tin) and no other powder metal or alloying additives. In this regard, it is contemplated that the formulation may be a closed-ended composition including only these powder metals (including any lubricant and ceramic additives).
[0029] Additionally, it should be noted that while specific powders are provided as described above, there may be slight variations in sourcing, and in some cases, slight variations in powder type (e.g., instead of one type of aluminum powder, two or more "pure" aluminum powder metals with varying powder size distributions may be mixed).
[0030] While a target composition is provided to arrive at a composition of Al-0.7Mg-0.4Si-xSn having a tin content where "x" in xSn is between 0.0 and 1.0 wt. % (and values of "x" of 0.0, 0.25, 0.5, and 1.0 are specifically discussed in the examples below), it should be noted that the target composition for either or both of the magnesium and silicon can also be expanded or modified to some extent. For example, the weight percentage of silicon in the powder metal composition may be within the range of between 0.2 wt % and 0.6 wt % (or a narrower range of between 0.3 wt % and 0.5 wt %, or an even narrower range of between 0.35 wt % and 0.45 wt %) of the powder metal composition, and the weight percentage of magnesium in the powder metal composition may be within the range of between 0.5 wt % and 0.9 wt % (or a narrower range of between 0.6 wt % and 0.8 wt %, or an even narrower range of between 0.65 wt % and 0.75 wt %) of the powder metal composition.
[0031] For the aluminum powder metal, as shown in Table I, the powder metal is 99.7 weight percent aluminum, and this powder metal is considered to be essentially aluminum only, with ineffective trace elements.
[0032] Additionally, as generally described above, it is contemplated that up to 15% by volume of a ceramic powder additive may be provided to produce a metal matrix composite with a view to improving the wear resistance and strength of the as-sintered part. The ceramic powder additive may be characterized as aluminum nitride (AlN), which is primarily contemplated as an additive to powder metal compositions, as described below, although silicon carbide (SiC) and aluminum (Al2O3) are other ceramic additives that are contemplated as possible additives.
[0033] For aluminum nitride (AlN) MMC additives, it is contemplated that these aluminum nitride additives may be, for example, aluminum nitride grade AT (agglomerated powder with a broader particle size distribution) or aluminum nitride grade BT (a crushed powder with a relatively fine particle size). Both grades can be applied to such powder metal formulations, the difference being in their response to processing and properties.
[0034] Both Grade AT and Grade BT aluminum nitride have a hexagonal crystal structure and are single-phase. To chemically characterize these aluminum nitride additives, by mass fraction, both Grade AT and Grade BT have a minimum of 32% nitrogen, a maximum of 0.15% carbon, and a maximum of 0.05% iron. However, Grade AT has a maximum of 1.3% oxygen, while Grade BT has a maximum of 1.5% oxygen. Grade AT has a 2.0m 2 / g, whereas Grade BT has a specific surface area of 1.8m 2 / g to 3.8m 2 / g The particle size distributions of the two different grades are shown in Table II below. [Table 3]
[0035] Aluminum nitride as an MMC additive can improve the wear resistance, ductility, and thermal conductivity of powder metal formulations, with minimal tool wear compared to more traditional MMC additives such as Al2O3 or SiC.
[0036] When ceramic powder additives are used, the various powder metals, aluminum nitride or other ceramic additives, and lubricants are mixed together during powder preparation, preferably in a high intensity mixer, to uniformly distribute the various particles, especially fine particles, throughout the powder metal composition mixture and to avoid segregation phenomena.
[0037] Turning to the collected experimental data, four alloys were studied as powder metal equivalents to 6063 wrought aluminum alloy, all containing the same concentrations of magnesium and silicon, differing only in the amount of tin added. All four variations were made by mixing the powder metal in Table I above with enough Al-12Si powder metal to achieve 0.4% silicon by weight of the overall powder metal composition, and enough elemental magnesium powder metal to achieve 0.7% magnesium by weight of the overall powder metal composition. Approximately 1.5% by weight of LicoWax® C was also added. The only variable in the mixture was tin, with powder metal composition mixtures made with no tin (0.0% by weight tin), 0.25% by weight tin, 0.5% by weight tin, and 1.0% by weight tin. For simplicity and accuracy, the experimental sample data provided in the figures and not designated as "forged" can be estimated to be aluminum with 0.4 wt. % silicon, 0.7 wt. % magnesium, and the indicated amount of tin, but the samples are identified only by their respective tin content (optionally in combination with various processing conditions or heat treatments).
[0038] The following methods were used for alloy preparation and manufacturing of the powder metal samples investigated.
[0039] First, the initial powders were mixed in the appropriate proportions using a Turbula shaker mixer. The alloying additions were added sequentially to the required base aluminum powder, allowing time for mixing between each addition to ensure good mixing.
[0040] Once the powder metals were prepared, transverse rupture strength (TRS) bars were die compacted into compacts (nominal 31.7 mm x 12.7 mm x 9.7 mm). Each sample was prepared from 10 g of a target powder metal composition (again, differing chemically only in tin content) and compacted at various forming pressures (compaction pressures) between 150 MPa and 550 MPa.
[0041] The samples were sintered sequentially in a tube furnace with multiple heating elements that allowed uniform heating of the compact in a controlled nitrogen atmosphere.
[0042] Various data and studies have been conducted to evaluate the properties of samples of powder metal aluminum alloy compositions and to tailor potential processing parameters for the compositions.
[0043] Referring to Figures 1A, 1B, 1C, and 1D, the effect of sintering temperature on density, hardness, mass change, and dimensional change is shown. In Figures 1A, 1B, 1C, and 1D, compact samples were molded at 250 MPa and sintered for 20 minutes at 5°C increments between 610°C and 640°C for various tests. As can be observed, the samples differed in chemistry by having a composition of Al-0.7Mg-0.4Si-xSn, where "x" in xSn is one of 0.0 wt%, 0.25 wt%, 0.5 wt%, and 1.0 wt% tin content. Findings from a comparative study of sintering temperature and tin chemical content are as follows:
[0044] First, Figure 1A shows that for chemistries that achieve moderate densities, optimal densification begins to plateau at 630 °C. That is, all three chemistries, Al-0.7Mg-0.4Si-0.25Sn, Al-0.7Mg-0.4Si-0.5Sn, and Al-0.7Mg-0.4Si-1.0Sn, have densities that sinter to approximately 98% or greater of theoretical density at sintering temperatures above 630 °C. Only the Al-0.7Mg-0.4Si-0.0Sn (no tin) sample struggled to densify, achieving less than 96% of theoretical density when sintered at 640 °C for 20 minutes.
[0045] Second, Figure 1B shows that the maximum average hardness for the tin-containing materials is reached when sintered at 635°C for 20 minutes, compared to when sintered at higher or lower temperatures for similar times.
[0046] Third, as shown in Figure 1C, the mass change of the tin-containing composition is approximately 1.5% when sintered at any temperature between 610°C and 640°C. This mass loss is expected, considering that the lubricant was added in an amount of 1.5% of the total weight of the powder metal composition. The tin-free composition does not experience a comparable level of lubricant burn-off. The mass change of the tin-free sample reaches a mass loss of 1.35% at higher sintering temperatures (i.e., approximately 640°C), but at lower sintering temperatures (i.e., approximately 610°C), the mass loss is less than expected, remaining at approximately 1.15%.
[0047] Fourth, referring to Figure 1D, which shows dimensional change, shrinkage begins to level off or stabilize at about 630°C, which is generally consistent with the density leveling off in Figure 1A. Again, as reflected in this shrinkage data, it can be seen that the non-tin-containing composition struggles to sinter. The non-tin-containing composition only begins to exhibit some shrinkage at the highest temperature tested (640°C), and furthermore, it can be seen that it shrinks only about 0.7%, compared to about 2.0% shrinkage for the tin-containing sample at these higher temperatures.
[0048] Across all samples, the 0.25 wt% and 0.5 wt% tin samples appear to provide the best results for these tested properties. All sintered tin-containing samples exhibited favorable density and dimensional change, but differences existed in the observed average hardness. Most notably, at the upper end of the sintering temperature range investigated, the 0.25 wt% and 0.5 wt% tin samples exhibited higher average hardness than the 1.0 wt% tin sample. Thus, for optimally sintered Al-0.7Mg-0.4Si-xSn parts (i.e., above 630°C), some tin addition improved hardness compared to tin-free samples. However, based on the four chemistries tested, increasing tin beyond 0.25 wt% reduced the average hardness, with a slight decrease in average hardness between 0.25 and 0.5 wt% tin and a continuous decrease in average hardness between 0.5 and 1.0 wt% tin.
[0049] 2A, 2B, 2C, 2D, and 2E, the effect of compaction pressure was investigated for Al-0.7Mg-0.4Si-xSn compositions, where "x" in xSn is one of 0.0, 0.25, 0.5, and 1.0 wt% tin content. For these powder chemistries, compaction pressures of 150 MPa, 250 MPa, 350 MPa, 450 MPa, and 550 MPa were all investigated. Findings from these investigations include the following:
[0050] First, Figure 2A shows that the green strength increases significantly with increasing compaction pressure from 150 MPa to 250 MPa for all powder chemistries, and then decreases slightly from 250 MPa to 350 MPa. Furthermore, the green strengths are all higher than 10,000 kPa (the target strength line is shown at 7,500 kPa).
[0051] Figure 2B shows the effect of compaction pressure on the sintered density of compacted parts compressed at various compaction pressures and then sintered at 635°C for 20 minutes. All three tin-containing samples consistently have densities greater than 98% of theoretical density at all pressures, with densities greater than about 98.8% of theoretical density at compaction pressures above 250 MPa. The tin-free sample (Al-0.7Mg-0.4Si-0.0Sn) or "0.0Sn" has a relatively low density across the entire range of compaction pressures, only exceeding 95% of theoretical density at the highest compaction pressure tested (550 MPa).
[0052] Figure 2C shows the effect of compaction pressure on average hardness for parts sintered at 635°C for 20 minutes. While the average hardness of the tin-free samples remains relatively low, the compositions containing tin (represented by the bars located to the right of each bundle at each compaction pressure) show a fairly consistent trend in average hardness over the range of compaction pressures from 250 MPa to 550 MPa.
[0053] Referring to Figure 2D, the mass change during sintering (again, 635°C for 20 minutes) at multiple compaction pressures generally matches the results in Figure 1D, with all tin-containing samples showing approximately 1.5% mass loss (consistent with the addition of lubricant), and the tin-free samples showing a smaller mass loss of 1.3%, tapering off slightly with increasing compaction pressure.
[0054] Finally, referring to Figure 2E, the dimensional reduction of several sintered samples (again, 635°C for 20 minutes) is shown at various compaction pressures. Initially, consistent with the conclusions drawn from Figure 1D, this figure confirms that the tin-containing samples have significantly greater reduction relative to the tin-free samples. However, the chart further shows that as the compaction pressure increases from 150 MPa to 250 MPa, the degree of reduction decreases significantly, later leveling off at approximately -1.5% for the tin-containing samples. This difference between 150 MPa and 250 MPa can be interpreted as the samples compacted at the lower pressure having a significantly lower density in the green state and therefore a greater dimensional change when sintered.
[0055] The effect of sintering time on density, average hardness, mass change, and dimensional change is further explored with reference to Figures 3A, 3B, 3C, and 3D. For these four figures, various samples were compacted at a pressure of 350 MPa and sintered at 635°C for 5, 10, 15, 20, 25, and 30 minutes. Again, as with other studies described above, the samples differ from each other in elemental tin (0.0 wt%, 0.25 wt%, 0.5 wt%, and 1.0 wt%).
[0056] Figure 3A shows that densification begins to plateau at 20 minutes, and as with other studies discussed above, the tin-containing compositions outperform the tin-free compositions. For the tin-containing compositions, no significant differences were observed across the various amounts of tin. That is, the 0.25 wt%, 0.5 wt%, and 1.0 wt% tin concentrations all converged to densities between 98.5% and 99.0% of theoretical, corresponding to sintering times between 20 and 30 minutes.
[0057] Referring to Figure 3B, the average hardness is shown for various sintering times and chemical compositions. The average hardness of the compositions containing 0.25 and 0.5 wt% tin is higher than the average hardness of the compositions without tin and the composition containing 1.0 wt% tin, and the data suggests a potential bimodal peak.
[0058] Figures 3C and 3D show the mass change and dimensional change, respectively, which are minimally affected by changes in sintering time. Again, as with the samples above, the tin-containing compositions show greater mass loss and dimensional change compared to the tin-free compositions, but there is no significant difference between samples sintered for 5 minutes and 30 minutes.
[0059] Figures 4A, 4B, and 4C show the effect of sizing pressure (100 MPa, 200 MPa, 300 MPa, and 400 MPa) on the dimensional change, density, and average hardness of parts made from Al-0.7Mg-0.4Si-0.25Sn and Al-0.7Mg-0.4Si-0.5Sn powder metal compositions, respectively. The samples were compacted at 350 MPa, sintered at 635°C for 20 minutes, and sized.
[0060] Figure 4A shows the effect of varying sizing pressure on the percentage change in overall length (OAL). From this figure, it can be seen that above a sizing pressure of 200 MPa, there is a diminishing return in size reduction with increasing pressure. This appears to be primarily due to the relatively high density of the as-sintered parts. On the other hand, Figure 4B shows that there is some improvement in densification with increasing sizing pressure, but this is quite marginal (note that the scale in Figure 4B is from 98.5% to 99.5% of theoretical density). While the sample containing 0.5 wt% tin exhibits better initial densification, further compression provides only minimal improvement, while the sample containing 0.25 wt% tin exhibits a greater effect of pore shrinkage and elimination as pressure increases.
[0061] Figure 4C shows the effect of sizing pressure on average hardness. The data in this chart shows that hardness increases steadily with increasing sizing pressure, and that at all stages of sizing pressure, the samples containing 0.25 wt% tin maintain a slightly higher average hardness than the samples containing 0.5 wt% tin.
[0062] 5A, 5B, 5C, and 5D, the effect of sizing and chemistry (i.e., varying tin content) on Young's modulus, ultimate tensile strength (UTS), yield strength, and maximum elongation are shown and compared to forged samples. These powder metal samples were compacted at 350 MPa, sintered at 635°C for 20 minutes, and then sized at 120 MPa in an unconstrained die.
[0063] 5A, the 0.25 wt% and 0.5 wt% tin samples are fabricated from powder metal with Young's moduli comparable to those found in the literature (all "references" being compared are found in ASM Handbook, Volume 2: Properties and Selection, page 407). The tin samples, especially the 0.25 wt% and 0.5 wt% tin samples, perform significantly better than non-specified 6063 forgings.
[0064] Figure 5B shows that the ultimate tensile strengths of the sintered and sized powder metal parts are lower than the ultimate tensile strengths (UTS) of 6063 forgings subjected to the T1 and T5 processes (again, both of which are described in the ASM Handbook, Volume 2). In all cases, the UTS of the powder metal parts is lower than the literature forgings, but the difference between the values for the sintered and sized tin-containing powder metal parts and the literature-derived 6063-T1 forgings is relatively small. That is, the UTS value for the tin-containing powder metal parts is approximately 130 MPa, while the UTS value for the literature-derived 6063-T1 forgings is approximately 150 MPa. However, this gap is significantly larger between the powder metal parts and the 6063-T5 forgings.
[0065] FIG. 5C shows that the yield strength of the powder metal sintered and sized part actually exceeds that of the comparative 6063-T1 forging from the literature, and that while tin-containing powder metal parts are typically above 90 MPa, they are significantly less than the 6063-T5 forging, which has a yield strength of just over 140 MPa.
[0066] A comparison of maximum elongation is shown in Figure 5D. The literature 6063-T1 forging has a maximum elongation of 20%, exceeding the elongation of the sintered and sized powder metal part. However, the powder metal part made from the tin-containing composition has a maximum elongation between 12% and 15%, comparable to the literature 6063-T5. Meanwhile, the part made from the tin-free composition has a significantly lower maximum elongation (only around 2%).
[0067] Figures 6A, 6B, 6C, and 6D show further comparisons of Young's modulus, UTS, yield strength, and maximum elongation data for Al-0.7Mg-0.4Si-0.5Sn ("0.5Sn" samples) compositions that were sintered and sized or subjected to the T8 heat treatment. Powder metal samples were compacted at 350 MPa and sintered at 635°C for 20 minutes. For samples subjected to the T8 heat treatment, they were solution annealed at 520°C for 2 hours, sized in an unconstrained die at 120 MPa, and aged at 175°C for 22 hours.
[0068] Figure 6A shows that the Young's modulus of the 0.5 wt% tin samples that were sintered and sized or subjected to the T8 heat treatment exceeded that of 6063-T8 forgings from the literature or 6063 forgings with unspecified tempers. The T8 powder metal parts performed slightly better than the sintered and sized parts; specifically, the T8 samples had Young's moduli of over 80 GPa, while the sintered and sized parts had Young's moduli of about 75 GPa.
[0069] Figure 6B shows that after the T8 heat treatment (~240 MPa), the UTS of the 0.5 wt. % tin sample was comparable to and slightly exceeded that of the comparative 6063-T8 forged sample and exceeded the UTS values of the 6063-T1 and 6063-T5 forged samples from the literature. The sintered and sized 0.5 wt. % tin sample exhibited less impressive UTS values, but was nearly equivalent to the 6063-T1 forged samples. Similarly, Figure 6C shows that after the T8 heat treatment, the 0.5 wt. % tin sample had a yield strength slightly above 200 MPa, significantly exceeding both the comparative 6063-T8 forged data and the literature data. Again, the sintered and sized 0.5 wt. % tin sample performed less impressively, but exceeded the yield strength of the 6063-T1 forged samples from the literature.
[0070] Figure 6D shows the performance tradeoff for a 0.5 wt. % tin sample when subjected to the T8 heat treatment instead of the sintered and sized treatment. In this figure, the powder metal sample subjected to the T8 heat treatment is shown to have a maximum elongation of only 6%. The comparative 6063-T8 forging has a maximum elongation of 15%. The sintered and sized 0.5 wt. % tin sample has a maximum elongation of about 15% similar to the 6063-T8 forging, but as noted above, the sintered and sized part does not perform as well in terms of the other measured mechanical metrics.
[0071] Referring to Figures 7A and 7B, the aging response is shown for sintered parts made from Al-0.7Mg-0.4Si-0.25Sn and Al-0.7Mg-0.4Si-0.5Sn compositions. Both curves are based on parts compacted at 350 MPa and sintered at 635°C for 20 minutes. Figure 7A shows the natural aging curve (time is displayed on a logarithmic scale), while Figure 7B shows the T8 aging process, in which the part was further solution-annealed at 520°C for 2 hours, sized at a 3.5% reduced pressure, and aged at 175°C.
[0072] From Figure 7A, it can be seen that the Al-0.7Mg-0.4Si-0.25Sn sample exceeded 30 HRE after approximately 30 days, while the Al-0.7Mg-0.4Si-0.5Sn sample had approximately 22 HRE after 30 days. For the Al-0.7Mg-0.4Si-0.25Sn sample, hardening appears to begin between 24 hours and 4 days and to end sometime between 4 and 9 days. For the Al-0.7Mg-0.4Si-0.5Sn sample, hardening appears to begin and end between 4 and 9 days. In either event, the Al-0.7Mg-0.4Si-0.25Sn sample consistently had better hardness than the Al-0.7Mg-0.4Si-0.5Sn sample at post-sintering times.
[0073] As shown in Figure 7B, when a sample with a composition of Al-0.7Mg-0.4Si-0.5Sn is artificially aged, the hardness peaks at about 6 hours and remains at a plateau until about 24 hours. The peak hardness in this range is about 81 HRE.
[0074] Finally, and perhaps most importantly and impressively for practical applications, the thermal properties of the powder metal formulations were evaluated. This thermal properties data is significant in that one potential use of 6063-equivalent powder metal formulations is in the manufacture of parts with potential thermal applications (e.g., battery terminals and thermal management applications).
[0075] In this application, the full set of data is not provided, but the thermal conductivity equation is k=αρc P where α is the thermal diffusivity, ρ is the density, and c P is the specific heat capacity. Note that a correction is made to account for thermal expansion at a particular temperature.
[0076] An investigation was conducted to determine how parts made from powder metal compositions thermally behaved compared to forgings and how further T8 heat treatment affected the thermal properties of the samples. A summary of the results is provided below. Regarding specific heat capacity, it was found that 6063 forgings exhibited an improved specific heat capacity in the T8 state (compared to 6063 forgings that had not undergone T8 treatment), whereas the heat capacity of Al-0.7Mg-0.4Si-0.5Sn showed negligible improvement between the as-sintered and T8 states. Meanwhile, powder metal parts showed a clear improvement in thermal diffusivity in the T8 state compared to the as-sintered state. However, no improvement in thermal diffusivity was observed when the 6063 forgings were subjected to T8 treatment.
[0077] The resulting effect, as best understood, is that the T8 treatment improved the thermal conductivity of both the 6063 forgings disclosed herein and the equivalent powder metal compositions, albeit for different reasons. In sintered powder metal parts, the improved thermal conductivity is not attributed to an improved specific heat capacity (as in the forged material), but rather to an improved thermal diffusivity.
[0078] Thermal conductivity data are shown in Figures 8A and 8B. In Figure 8A, the thermal conductivity at various temperatures is measured for each of the Al-0.7Mg-0.4Si-0.0Sn, Al-0.7Mg-0.4Si-0.25Sn, Al-0.7Mg-0.4Si-0.5Sn, and Al-0.7Mg-0.4Si-1.0Sn powder metal compositions and compared to 6063-T5. Figure 8A shows that the thermal conductivity of the tin-containing powder metal samples (already sintered and sized) is inferior to that of the 6063-T5 forgings, but still has excellent thermal conductivity for a powder metal part. In particular, the Al-0.7Mg-0.4Si-0.5Sn composition has surprisingly good thermal conductivity for a powder metal, ranging from 190 W / (m·K) to 205 W / (m·K) over the temperature interval between 100°C and 200°C. While there is an observed decrease in thermal conductivity above about 200°C for all powder metal composition samples, the Al-0.7Mg-0.4Si-0.5Sn composition sample performs very well up to that point; in fact, the decrease in data at 250°C is likely attributable to a thermal event and not indicative of actual conductivity at that temperature.
[0079] 8B shows comparative data for parts made from the Al-0.7Mg-0.4Si-0.5Sn composition, where the sized and sintered parts are compared to parts subjected to the T8 heat treatment described above. The Al-0.7Mg-0.4Si-0.5Sn sample subjected to the T8 heat treatment exhibited improved thermal conductivity between 200°C and 250°C, demonstrating the potential of this powder metal composition for thermal applications such as heat sinks and battery terminals.
[0080] To further illustrate the effect of the AlN addition on material properties and to provide additional data on samples subjected to the T8 process, comparative data was also collected between parts made from a composition designated "PM6063" and parts made from PM6063 with 1% by volume AlN added ("PM6063-AlN"). Table III below lists the specific powder formulations or blends of PM6063 used to provide the metal matrix for the comparative samples. [Table 4]
[0081] Each sample made from this powder composition will subsequently be referred to in the samples below as "PM6063" or "PM6063-AlN," where the "-AlN" designation is used to indicate samples made from this composition but with a targeted 1% by volume aluminum nitride MMC addition. These compositions are not 6063 compliant, but are targeted to be powder metal compositions with performance equivalent to 6063 forgings.
[0082] For each of the PM6063 and PM6063-AlN blends, 50 transverse fracture strength (TRS) bars, 5 Charpy bars, and 5 Falex packs (50 mm OD x 12 mm L) were molded and sintered from each blend to a green density of 2.50 g / cc. Initially, 15 TRS bars from each composition were sintered at different thermal profiles, and the dimensional change, mass change, average hardness, and sintered density of all TRS bars were measured to identify the optimal conditions (since optimal conditions may vary from furnace to furnace). All remaining TRS bars, along with the Charpy and Falex packs, were sintered at the optimal conditions identified during the initial sintering and testing of the 15 TRS bars.
[0083] For the samples prepared under the optimum sintering conditions, five TRS bars from each of the PM6063 and PM6063-AlN samples were measured for dimensional change, mass change, average hardness, and sintered density after sintering. The results for dimensional change, mass change, average hardness, and sintered density after sintering are listed in Table IV below. [Table 5]
[0084] All remaining samples were subjected to a T8 heat treatment (targeting 2-3% RIH), which included solutionizing at 530°C (2 hours at this temperature), quenching, sizing to reduce AOL by 2%, and aging at 175°C for 8 hours. The average hardness of the samples subjected to the T8 heat treatment, and a comparison with the samples subjected to the T1 heat treatment, is shown in Table V below. [Table 6]
[0085] Charpy threaded-end tensiles were fabricated and subsequently measured for yield strength, ultimate tensile strength, Young's modulus, and total elongation at break for five specimens each of PM6063 and PM6063-AlN, and are shown in Table VI below. [Table 7] Again, and for clarity, these are the mechanical properties of samples made from the powder composition and subjected to a T8 heat treatment.
[0086] Samples of each composition treated by the T8 process were also subjected to a three-point bending fatigue step test, the results of which are shown in Table VII below. [Table 8] For ease of understanding, σa,x The notation is x% of the bar is 10 6 This is the value at which the confidence of passing the cycle changes by 50%, where x% is 10%, 50%, or 90% in Table VII above.
[0087] Additionally, thermal diffusivity was measured at room temperature by laser flash analysis on duplicate specimens machined from the T8 TRS bar. These average thermal diffusivity results are shown in Table VIII below. [Table 9]
[0088] From Tables V, VI, VII, and VIII above, it can be seen that when 1% by volume of AlN is added to a powder metal composition, most material properties are comparable or may even be slightly degraded compared to a comparison sample without AlN as an additive, with the notable exception of the thermal diffusivity of 81.0 mmHg with the addition of AlN. 2 / s to 85.1mm 2 / s.
[0089] Referring to Figures 9A through 9D, the results of anodizing on PM6063 and PM6063-AlN are shown. Figures 9A and 9B show "PM6063" and "PM6063-AlN" samples, where "PM6063" corresponds to the powder metal formulation equivalent to 6063 forging, which is actually Al-0.7Mg-0.4Si-0.5Sn (again, not the equivalent of the 6063 forging formulation). Figure 9A shows the as-sized surfaces of two sets of samples, while Figure 9B shows the surfaces of two sets of samples after polishing with 240-grit SiC paper. Finally, Figure 9C shows the appearance change before and after anodizing, showing the results of the powder metal formulation and the addition of 1 volume percent AlN to the powder metal formulation for the as-sized samples, respectively. Figure 9D shows the change in appearance before and after anodizing for the polished samples with and without the powder metal formulation and with 1 vol% AlN added to the powder metal formulation, where the hard anodized surface appears black while the clear anodized surface maintains a gray appearance. In each "after" set, there were two samples that were hard anodized (in FIG. 9C, the bottom two samples correspond to "PM6063," in FIG. 9C, the top two samples correspond to "PM6063+1% AlN," in FIG. 9D, the bottom two samples correspond to "PM6063," in FIG. 9D, the top two samples correspond to "PM6063+1% AlN") and one sample that was clear anodized (in FIG. 9C, the top sample corresponds to "PM6063," in FIG. 9C, the bottom sample corresponds to "PM6063+1% AlN," in FIG. 9D, the top sample corresponds to "PM6063," in FIG. 9D, the bottom sample corresponds to "PM6063+1% AlN").
[0090] 10A-10D show anodized layers treated with a hard anodizing process. 10A and 10B show samples anodized after sizing, while 10C and 10D show samples anodized after polishing. 10A and 10C show "6063-HA Sized" and "6063-HA Polished," which refer to powder metal versions equivalent to the 6063 alloy described above that have been anodized after sizing or polishing, respectively, while 10B and 10D show "6063-AlN-HA Sized" and "6063-AlN-HA Polished," which refer to powder metal versions equivalent to the 1% AlN-added 6063 alloy described above that have been anodized after sizing or polishing, respectively. From the comparative side views of these anodized layers, it can be seen that the anodized layer of the sized-only sample (FIG. 10A) is rougher than the anodized layer of the AlN-added powder metal sample (FIG. 10B), and that both polished samples (FIGS. 10C and 10D) are relatively smooth.
[0091] Surface finish data are provided for the samples shown below in Table IX (corresponding to powder metal formulations equivalent to 6063 alloy) and Table X (corresponding to formulations where 1% by volume of AlN is added to powder metal equivalent to 6063 alloy). [Table 10] [Table 11]
[0092] The data in Tables IX and X show that the average surface roughness (Ra) of the polished samples is lower compared to the sized-only samples. Similarly, the difference between the highest peak and deepest valley (Rz) is lower for the polished samples than for the sized samples for each material. This is generally consistent with the cross-sectional diagrams and observations of the layer structure.
[0093] It is to be understood that various other modifications and variations to the preferred embodiment can be made within the spirit and scope of the present invention. Accordingly, the present invention should not be limited to the described embodiments. Reference should be made to the claims to ascertain the full scope of the present invention.
Claims
1. 1. A powder metal composition which can be compacted, sintered, and heat treated to provide a powder metal material equivalent to 6063 wrought aluminum alloy, comprising: an aluminum powder metal containing no pre-alloyed alloying additives, except for unavoidable non-effective trace substances; aluminum-silicon powder metal; Elemental magnesium powder metal; optional elemental tin powder metal; an optional ceramic powder additive to provide a metal matrix composite upon sintering, which is not taken into account when calculating the percentage of alloy in said powder metal composition; a lubricant, the weight of which is excluded from the weight percentage of each alloying element, because it is burned off during sintering of the powder metal composition; Equipped with the weight percentage of silicon in said powder metal composition is in the range of 0.2% to 0.6% by weight of said powder metal composition; the weight percentage of magnesium in said powder metal composition is in the range of 0.5% to 0.9% by weight of said powder metal composition; 1. A powder metal composition, wherein the weight percentage of tin in said powder metal composition is in the range of 0.0% to 1.0% by weight of said powder metal composition.
2. the weight percentage of the silicon in the powder metal composition is within the narrower range of 0.3% to 0.5% by weight of the powder metal composition; the weight percentage of the magnesium in the powder metal composition is within the narrower range of 0.6% to 0.8% by weight of the powder metal composition.
10. The powder metal composition of claim 1.
3. the weight percentage of the silicon in the powder metal composition is within the narrower range of 0.35% to 0.45% by weight of the powder metal composition; the weight percentage of the magnesium in the powder metal composition is within the narrower range of 0.65% to 0.75% by weight of the powder metal composition.
3. The powder metal composition of claim 2.
4. the weight percentage of said silicon in said powder metal composition is 0.4 weight percent of said powder metal composition; a weight percentage of said magnesium in said powder metal composition being 0.7% by weight of said powder metal composition; 3. The powder metal composition of claim 2.
5. 10. The powder metal composition of claim 1, wherein the aluminum powder metal is at least 99.7% by weight aluminum.
6. 2. The powder metal composition of claim 1, wherein the aluminum-silicon powder metal is an Al-12Si master alloy powder metal having 88% by weight aluminum and 12% by weight silicon.
7. 10. The powder metal composition of claim 1, wherein the weight percentage of the tin in the powder metal composition is within the narrower range of 0.25% to 0.75% by weight of the powder metal composition.
8. 8. The powder metal composition of claim 7, wherein the weight percentage of the tin in the powder metal composition is 0.5% by weight of the powder metal composition.
9. 10. The powder metal composition of claim 1, wherein the ceramic powder additive is less than 15 volume percent of the powder metal composition.
10. 10. The powder metal composition of claim 9, wherein the ceramic powder additive is aluminum nitride.
11. The aluminum nitride is 2.0 m 2 11. The powder metal composition of claim 10, characterized in that it has a specific surface area of less than or equal to 1.5 μm / g, a particle size distribution of D 10% in the range of 0.4 μm to 1.4 μm, a particle size distribution of D 50% in the range of 6 μm to 10 μm, and a particle size distribution of D 90% in the range of 17 μm to 35 μm.
12. The aluminum nitride is 1.8 m 2 / g to 3.8m 2 11. The powder metal composition of claim 10, characterized in that it has a specific surface area in the range of 0.2 μm to 0.6 μm, a D 50% particle size distribution in the range of 1 μm to 3 μm, and a D 90% particle size distribution in the range of 5 μm to 10 μm.
13. 11. The powder metal composition of claim 10, wherein the aluminum nitride (AlN) has a hexagonal crystal structure and is single phase.
14. 11. The powder metal composition of claim 10, wherein the ceramic powder additive is silicon carbide (SiC).
15. A green compact formed from the powder metal composition of claim 1.
16. 16. A sintered powder metal part formed from the green compact of claim 15.
17. 17. The sintered powder metal part of claim 16, wherein the powder metal portion has a thermal conductivity in the range of 190 W / (m·K) to 205 W / (m·K) within a temperature range of 100° C. to 200° C.
18. 17. The sintered powder metal part of claim 16, wherein the powder metal portion has an ultimate tensile strength in the range of 100 MPa to 140 MPa and a yield strength in the range of 90 MPa to 105 MPa.
Citation Information
Cited By
Aluminum alloy powder sintered body
JP7843011B1